Caucasian-specific allele in non-synonymous single nucleotide polymorphisms of the gene encoding deoxyribonuclease I-like 3, potentially relevant to autoimmunity, produces an inactive enzyme - Ueki, Misuzu; Takeshita, Haruo; Fujihara, Junko; Iida, Reiko; Yuasa, Isao; Kato, Hideaki; Panduro, Arturo; Nakajima, Tamiko; Kominato, Yoshihiko; Yasuda, Toshihiro (Clinica chimica acta, 2009)
Deoxyribonuclease I-like 3 (DNase Il3), a member of human DNase I family, is postulated to be involved in the genesis of autoimmune diseases. In the DNase Il3 gene, 2 non-synonymous SNPs, R178H and R206C, have been identified, however relevant population data are not available. Genotyping of the SNPs was performed in healthy subjects belonging to 3 ethnic groups ( n = 1708), including nine different populations, using an amplification refractory mutation system and the PCR-RFLP technique. All of the 9 populations were typed as a single genotype in R178H. All Asian and African populations exhibited only a homozygous C686 allele in R206C, whereas a heterozygote, C686/T686, was found (frequency of 3.5–15.4%) in three Caucasian populations (Turk, German and Mexican); Caucasian-specific allele T686 was identified. The substitution of Arg by Cys corresponding to R206C resulted in elimination of DNase Il3 activity. A Caucasian-specific allele in SNP R206C produces an inactive form of DNase Il3. It seems plausible that levels of DNase Il3 activity in Caucasian subjects with the heterozygote in R206C are lower than those in individuals with the predominant homozygote. Our results may have clinical implications in relation to the prevalence of autoimmune diseases.